+0  
 
0
108
2
avatar+311 

Simplify $\left( \frac{4}{x} \right)^{-1} \left( \frac{3x^3}{x} \right)^2 \left( \frac{1}{2x} \right)^{-3}$.

 

Soruce: Alcumus.

blush

 Mar 28, 2021
 #1
avatar+311 
+1

Nevermind, I got it right, I just forgot about the 2...blush

 

$\left( \frac{4}{x} \right)^{-1} \left( \frac{3x^3}{x} \right)^2 \left( \frac{1}{2x} \right)^{-3} = \frac{x}{4} \cdot (3x^2)^2 \cdot (2x)^3 = \frac{x}{4} \cdot 9x^4 \cdot 8x^3 = \boxed{18x^8}$. laugh

 Mar 28, 2021
edited by WillBillDillPickle  Mar 28, 2021
edited by WillBillDillPickle  Mar 28, 2021
 #2
avatar+2124 
0

Ohh, nice job. :))

 

=^._.^=

catmg  Mar 28, 2021

4 Online Users

avatar